A Single-Center, Randomized, Double-Blind, Placebo-Controlled Clinical Trial of the Effectiveness of ANT1 Soybean Extract Cream on Skin Recovery After Nd: YAG Laser Treatment. (February 2018) - Hsieh, Meng-Chien; Wu, Yi-Chia; Huang, Shu-Hung; Kuo, Yur-Ren; Lee, Su-Shin
Abstract : Nd:YAG laser has been used extensively for its versatility in treating many common aesthetic problems, but numerous adverse effects are often complained by recipients of Nd:YAG laser. This study introduces the ANT1 soybean extract cream, which was formulated to alleviate adverse effects after laser therapy. This study explores whether ANT1 enhances the repair mechanism of the postlaser skin, decreases laser-induced complication, and shortens recovery time. The study also aims to pinpoint the ANT1 concentration that is most effective in improving the skin condition after Nd-YAG laser therapy. Materials and Methods: This study was a single-center, randomized, double-blind, placebo-controlled trial. Patients eligible for the study were Asian women, aged 25 to 40 years, who were free of dermatological diseases and allergic reaction. There were a total of 45 subjects. Each subject received a session of Nd-YAG laser therapy every 2 weeks, totaling 3 sessions. Facial skin assessment was achieved via VISIA complexion analysis. VISIA complexion analysis quantitatively assessed the skin condition and tracked the recovery progress of each subject at baseline, immediately after all 3 laser sessions, and a week after the final laser treatment. Results: Skin condition was evaluated by VISIA complexion analysis. Skin condition was recorded in aspects of pigmented spots, wrinkles, texture, pores, and red area. After Nd-YAG laser therapy, postlaser inflammation was observed in all subjects. Throughout the laser sessions and the outpatient follow-up clinic, the adverse effects of laser therapy, such as redness, spots, wrinkles, pores, and textures, decreased with the use of ANT1 cream. There has been a marked effect in wrinkle reduction in the patients who received a higher concentration of ANT1 cream ( P ⩽ 0.05). Statistically significant improvement in spots and pores is also seen ( P ⩽ 0.05). Conclusions: Through this study, the results suggest that the application of ANT1 soybean extract cream ameliorates the complications and enhances the cosmetic effects of Nd-YAG laser therapy. A higher concentration of the ANT1 cream significantly reduces wrinkles and redness after laser. All in all, this study proves that the ANT1 soy extract cream may be a useful addition to postlaser care for an overall enhancement in skin condition and recovery.